2001
DOI: 10.1097/00125817-200103000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human acid ??-glucosidase enzyme therapy for infantile glycogen storage disease type II: Results of a phase I/II clinical trial

Abstract: This phase I/II first study of recombinant human GAA derived from CHO cells showed that rhGAA is capable of improving cardiac and skeletal muscle functions in infantile GSD-II patients. Further study will be needed to assess the overall potential of this therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
231
0
8

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 202 publications
(245 citation statements)
references
References 14 publications
6
231
0
8
Order By: Relevance
“…10 Long-term correction of GSD-II in GAA-KO/SCID mice F Xu et al GSD-II patients. 15,20 Recently, it has been demonstrated that restoration of a single muscle's contractile force can be achieved after intramuscular injection of an AAV vector encoding hGAA. 21 However, the evaluation of overall gross muscle strength has not been reported after attempting gene therapy using viral vectors in GSD-II animal models.…”
Section: Normalized Muscle Function After Extended Glycogen Clearancementioning
confidence: 99%
See 1 more Smart Citation
“…10 Long-term correction of GSD-II in GAA-KO/SCID mice F Xu et al GSD-II patients. 15,20 Recently, it has been demonstrated that restoration of a single muscle's contractile force can be achieved after intramuscular injection of an AAV vector encoding hGAA. 21 However, the evaluation of overall gross muscle strength has not been reported after attempting gene therapy using viral vectors in GSD-II animal models.…”
Section: Normalized Muscle Function After Extended Glycogen Clearancementioning
confidence: 99%
“…11 Similarly, in our previous studies of ERT in humans, the onset of anti-rhGAA antibodies have also been correlated with the lack of sustained skeletal muscle efficacy. 15 To both circumvent and prove that production of antihGAA antibodies is a significant problem potentially limiting the efficacy of both ERT or gene therapy approaches to the treatment of GSD-II, we have now developed a new, immune-deficient mouse model of GSD-II. This was achieved by interbreeding GAA-KO mice with severe combined immune-deficient (SCID) mice, generating double knockout, GAA-KO/SCID mice.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was hypothesized from the first clinical trials that the presence or absence of cross-reactive immunological material (CRIM) may affect prognosis (Amalfitano et al 2001). CRIM-negative patients are completely unable to form any precursor form of native enzyme, whereas patients who are able to produce some precursor form of abnormalor normal-size native enzyme are CRIM-positive.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with the most severe infantile form normally die within the first year of life, while in the milder late-onset forms, muscle weakness is the primary symptom and respiratory failure is the major cause of significant morbidity and mortality [1]. Enzyme replacement therapy (ERT) with recombinant human GAA (rhGAA, alglucosidase alfa) is currently the only available therapy for Pompe disease with remarkable success, but also with significant limitations including the high cost for life-long administration of high-dose enzyme, poor clinical outcomes caused by the formation of high-titer anti-rhGAA antibodies in the majority of patients, and reduced efficacy in the skeletal muscle [2][3][4][5]. Thus, there is an unmet need to develop improved therapies for Pompe disease.…”
Section: Introductionmentioning
confidence: 99%